Joana Hadjithomas : Khalil Joreige. (Zürich : JRP/Ringier, 2013)
Une conversation avec Dominique Abensour, Etel Adnan, Rabih Mroué, Jacques Rancière, Michèle Thériault, Jalal Toufic, Anton Vidokle
boek
Keywords: Hadjithomas, Joana; Joreige, Khalil